Determinants of family independence in caring for hebephrenic schizophrenia patients - Herlin Ferliana; Nyoman Anita Damayanti; Diana Nurfarida Aisyah; Nuh Huda; Dwi Ernawati (SAGE Publishing, 2020)
Background: Schizophrenic patients are very susceptible to recurrent incidences, therefore the family plays a key role in providing care as a part of the recovery team. This study aimed to determine the relationship between knowledge, perceptions, attitudes and support with family independence in caring for hebephrenic schizophrenic patients. Design and Methods: It was used a correlational analytic design with cross sectional approach, and consecutive sampling technique was used, which attained 57 respondents. The independent variables were knowledge, perceptions, attitudes, and support, while independence was the dependent variable, and both were measured using questionnaires, and Spearman rank test was used for data analysis. Results: The results indicate the presence of a relationship between knowledge, perceptions, attitudes, as well as support and family independence in caring for hebephrenic schizophrenia. In addition, the spearman rank test showed P-values of 0.008, 0.011, 0.032, and 0.027 in family knowledge, perception, attitudes and support, respectively, at <0.05. Conclusions: This study indicates the importance of family support in attempts to improve the self-esteem of schizophrenic patients. Based on this data, the hospital is expected to improve the family-based patient recovery program.